'School visit' improving sustainable environmental knowledge of youth living near forest borders. Issue 1 (June 2021) - Septiarini, R; Herdiansyah, H; Siregar, P G.; Gawi, J
Abstract: Environmental education needs to be applied to adolescent children to one day coexist and avoid conflict with wildlife in the forest. Still, the initiative makes environmentally-themed education strategies attractive to teens. To better understand the adolescent environment's educational landscape, this study focused on students in their teens. There was 2016-2017 conducting a School Visit' in 10 schools attended by 596 students in Aceh. The majority of the material emphasizes the effectiveness of game-based, rich with a fun approach that combines movement and interaction. The purpose of this study was to understand the extent of the effectiveness of the 'School Visit' program to increase knowledge related to forests and wildlife and provide input or other views on the program. This study used a review method with secondary data. The report results were positive. The knowledge of teenage students about forests and orangutans increased by 10 percent. The goal of the 'school visit' program gave the students a fresher feel so that they would be more interested in learning about forests and wildlife.